The Role of Environmentally Committed Operational Efficiency in Mediating the Impact of Good Corporate Governance, Capital Structure, and Firm Size on Corporate Performance - Endang Purwaningsih; Budiyanto Budiyanto; Suwitho Suwitho (Maneggio, 2025)
This study examines the mediating effect of Environmental-Friendly Operational Efficiency (EOBRL) on the relationship of Good Corporate Governance (GCG), capital structure, company size, and company performance of companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. It employed path analysis using SmartPLS 4.0 software. The results show that GCG directly improves performance because of its impact on EOBRL which encourages sustainable and efficient business operations. The study also shows that capital structure measured by Debt to Equity Ratio (DER) and Debt to Assets Ratio (DAR) improves performance by allowing investments into green technology and operational advancements. In addition, larger firms enhance EOBRL and performance as they are more able to invest in sustainability. EOBRL was found to be the most significant mediator of EOBRL in GCG, capital structure and company size and better performance due to increased environmental regulations in the industry. This research supports the notion that sustainability should drive operational efficiency and competitiveness in the long term. Further research may focus on specific sector’s issues, impacts of changing legislations, and the influence of technology on the development of EOBRL in different sectors